Catheter aided repositioning of a displaced permanent pacemaker lead - Sochman, J; Lefflerová, K; Vrbská, J; Kovác, J (Pacing and clinical electrophysiology, 1995)
A 91-year-old woman, who had a pacemaker implanted in 1977, underwent replacement of a pulse generator and lead in 1995 because of recurrent syncope. The new lead dislodged the next day and migrated to the pulmonary artery. Because of her dependence on continued pacing, repeated resuscitation was required. Considering her advanced age and the impact of cardiopulmonary resuscitation on her general condition, we attempted catheter aided repositioning of the pacemaker lead. The procedure was technically successful; lead position was stable and optimal pacing parameters were attained. She was discharged in good condition.
Keywords: Cardiac Catheterization; kardiostimulátor; Foreign-Body Migration; lidé; migrace cizích těles; senioři nad 80 let; Pacemaker, Artificial; srdeční katetrizace; Aged; Humans; senioři; Aged, 80 and over; ženské pohlaví; Female